PROFIL BERPIKIR KREATIF DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA - Dian Susanti (Universitas PGRI Adi Buana Surabaya, 2016)
This research will be based in the background by the problems often encountered by students that is completing a math problem, in particular the question of the story. Most students consider the intricate story is primarily a matter which could not be resolved in a practical way. Formulation of the problem in this research is